Isolation 3’-end Fragment of Pun1 gene from Capsicum frutescens L. cultivar Cakra Hijau - Juliandri, Ria Reinnata; Zairina, Shelly; Khasna, Elhah Nailul; ., Dahlia; Listyorini, Dwi (KnE Life Sciences, 2017)
Pun1 gene [A1] is the one of candidate gene that responsible to determine pungency in Capsicum. In previous researches, 1 310 bp fragment of 1 671 bp Pun1 gene from Capsicum frutescens L. cv. Cakra Hijau had been isolated. The purpose of this research was to isolate of 3’-end fragment and get full length of Pun1 gene from C. frutescens L. cv. Cakra Hijau. DNA isolation was done using modified procedure. The method used to isolate the gene was PCR with a pair of primer, forward primer 5’-GAA-GGT-GGC-AGA-AGA-ATC-AG-3’ and reverse primer 5’-TTG- TTG ACC-GTA-AAC-TTC-CG- 3’. The result successfully to get 715 bp length DNA fragment. The assembly of this fragment into previous research produced a full length of 1 671 bp Pun1 gene from C. frutescens L. cv. Cakra Hijau consist of 738 bp first exon fragment, 348 bp intron fragment, and 585 bp second exon fragment. Keywords: C. frustescens L. cv. Cakra Hijau; gene isolation; Pun1 gene.